Antenatal ultrasound value in risk calculation for Autism Spectrum Disorder: A systematic review to support future research. (September 2018) - Fulceri, Francesca; Guzzetta, Andrea; Athanasiadou, Argyro; Iaconianni, Laura; Scattoni, Maria Luisa
Highlights: Fetal ultrasound may be a useful tool for detecting fetuses/infants at high risk for autism. Literature on ultrasound in fetus at high risk for ASD are limited and inconclusive. Further prospective studies should investigate biometric data and fetal movements. Abstract: There is a growing research interest on the antenatal features of children with neurodevelopmental disorders. Indeed, it has been proved that the neurodevelopment is, at least partly, affected by processes occurring in fetal life and that the early neurodevelopmental disorders identification is essential to optimize long-term outcomes. This systematic review aims to summarize findings on antenatal ultrasound data, which are or might be considered early risk indexes of postnatal social impairments. We conducted systematic searches in Pubmed and PsychINFO databases to identify studies including fetal ultrasound measurements and postnatal neurodevelopmental outcome assessment. The bibliographic search included 3203 articles but after the assessment of the eligibility conducted by two independent researchers, only 26 studies were selected. Some alterations in ultrasound antenatal measurements (such as biophysical data, nuchal thickness and enlargement of cerebral ventricles) have been associated to autism spectrum disorder. However, data are still limited, controversial and not specific. Reported data are here discussed to strongly support studies on fetuses at high risk for autism spectrum disorder.